2015
DOI: 10.1371/journal.pone.0130475
|View full text |Cite
|
Sign up to set email alerts
|

Interference between Redroot Pigweed (Amaranthus retroflexus L.) and Cotton (Gossypium hirsutum L.): Growth Analysis

Abstract: Redroot pigweed is one of the injurious agricultural weeds on a worldwide basis. Understanding of its interference impact in crop field will provide useful information for weed control programs. The effects of redroot pigweed on cotton at densities of 0, 0.125, 0.25, 0.5, 1, 2, 4, and 8 plants m-1 of row were evaluated in field experiments conducted in 2013 and 2014 at Institute of Cotton Research, CAAS in China. Redroot pigweed remained taller and thicker than cotton and heavily shaded cotton throughout the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 50 publications
(91 reference statements)
6
43
0
2
Order By: Relevance
“…Weeds reduce overall yields in many crops, including cotton (Wood et al, 2002;Barnett and Steckel, 2013;Ma et al, 2015). Effect sizes for individual studies were <0.95 for 101 (58%) studies, between 0.95 and 1.05 for 43 (25%) studies (negligible cover crop effect), and >1.05 for 30 (17%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Weeds reduce overall yields in many crops, including cotton (Wood et al, 2002;Barnett and Steckel, 2013;Ma et al, 2015). Effect sizes for individual studies were <0.95 for 101 (58%) studies, between 0.95 and 1.05 for 43 (25%) studies (negligible cover crop effect), and >1.05 for 30 (17%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…The second one is to generalize the optimization model for selecting optimal geometry parameters of the cutter. The third one is to fuse the present method with some on-line chatter detection techniques [41,42] for high performance milling.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive interference of A. palmeri indicated that 10 plants per 9.1 m row resulted in a 45% reduction in canopy volume at 10 weeks after planting and reduced cotton biomass to 50% by 8 weeks after planting (Morgan et al, 2001). Similarly, A. hybridus can grow taller than cotton and can reach up to 3 m thereby, shade the crop plants (Ma et al, 2015b). This weed at a density of 0.3 plants per m of row could cause a yield reduction of around 50% (Ma et al, 2015b).…”
Section: Weed Flora and Their Competitiveness In Cottonmentioning
confidence: 99%
“…Similarly, A. hybridus can grow taller than cotton and can reach up to 3 m thereby, shade the crop plants (Ma et al, 2015b). This weed at a density of 0.3 plants per m of row could cause a yield reduction of around 50% (Ma et al, 2015b). To further enhance the problems, over-reliance on glyphosate for weed management is favouring many weeds to rapidly evolve resistance to this herbicide (Flessner et al, 2015;Webster and Grey, 2015).…”
Section: Weed Flora and Their Competitiveness In Cottonmentioning
confidence: 99%